2020
DOI: 10.31557/apjcp.2020.21.9.2661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Annexin A4 as a Biomarker in the Early Diagnosis of Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most prevalent cancer worldwide. Early detection of HCC is crucial to improve prognosis and survival. Nearly 30 % of HCC patients present with normal serum alpha fetoprotein (AFP), which highlights the need for new biomarkers for HCC. Annexin A4 (ANXA 4) is one of the annexin family with high expressions found in gastric, liver, lung, colorectal and ovarian cancers. Aim : to evaluate the clinical significance of ANXA 4 in the early diagnosis of HCC. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Then, analyzing proteins that were less abundant in DHD and CHD, Annexins A2 and A4 are both calcium-dependent phospholipid-binding proteins involved in exocytosis and are upregulated in different neoplasms, including hepatocellular carcinoma and liver fibrosis [35][36][37][38]. Interestingly, Annexin A4 is expressed only by epithelial cells and encodes a protein that has possible interactions with ATP, has anticoagulant activity in vitro, and also inhibits the activity of phospholipase A2, having a protective effect against inflammation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Then, analyzing proteins that were less abundant in DHD and CHD, Annexins A2 and A4 are both calcium-dependent phospholipid-binding proteins involved in exocytosis and are upregulated in different neoplasms, including hepatocellular carcinoma and liver fibrosis [35][36][37][38]. Interestingly, Annexin A4 is expressed only by epithelial cells and encodes a protein that has possible interactions with ATP, has anticoagulant activity in vitro, and also inhibits the activity of phospholipase A2, having a protective effect against inflammation [39].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of Lewis(y), a component of the structure of the ANXA4 membrane protein, induces the chemoresistance of ovarian cancer cells, and ultimately promoting the progression of ovarian cancer (38). It was reported that the increased serum level of ANXA4 might be a promising biomarker for the early detection of hepatocellular carcinoma (39). A recent study indicated that downregulation of ANXA4 by toosendanin could mediate cisplatin sensitization in non-small cell lung cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, AFP-L3 has not been recognized as a conventional diagnostic indicator of HCC. Saad et al reported in HCV-related HCC patients (n=30) that serum levels of annexin A4 (ANXA4) might be a promising biomarker for the early diagnosis of HCC [40].…”
Section: Clinical and Biochemical Markersmentioning
confidence: 99%